Kinship analysis of brook trout Salvelinus fontinalis during their breeding migration. Issue 5 (3rd May 2013) - Meli, A.; Fraser, D. J.
<x xml:space="preserve">Abstract</x> Microsatellite markers were used to test whether groups of pre‐spawning adult brook trout Salvelinus fontinalis from the same population and captured at the same location during their breeding migration comprised kin. Only weak evidence for kin associations was found at the onset of breeding: the proportion of kin captured at the same location was low and similar to the proportion found across all locations and the average relatedness of S. fontinalis captured at the same location was low. A dilution of kin associations from the feeding to breeding phase is hypothesized to stem from mainly natural mortality that reduces family size by the adult stage. The results illustrate the dynamic nature of kin associations between consecutive life stages, even within the same fish population.